The Role of Lipopolysaccharide and Tight Junction Protein-1 (Zo-1) Levels and Symbiosis of Black Rice Extract in Obese Patients - Armanto Makmun (Journal of Global Pharma Technology, 2020)
Excessive fat accumulation, which is commonly known as obesity, causes health problems for the community, such as metabolic disorders. Recent studies have shown that the gut micro biota is involved in the occurrence of metabolic disorders in obesity. The gut micro biota can regulate body weight by influencing metabolic processes, regulating the expression of host genes, increasing the ability to extract and store energy. Intestinal micro biota imbalance and increased plasma lipopolysaccharide (LPS) contribute to inflammation in obesity. The latest safe approach in cases of obesity is to use active ingredients from local foods. In South Sulawesi, Indonesia and also in other Asian countries found black rice as the local product that is very good for health because the high level of bioactive compounds that are important for health such as anthocyanin, proteins, amino acids, and phenolic acids. The ingredients in black rice play a role in modulating the composition of the intestinal micro biota as indicated by the increasing composition of Bifid bacterium and Lactobacillus. The increase in the composition of Bifid bacterium causes improvement in the expression of tight junction proteins in the intestinal epithelium, thereby contributing to prevent the translocation of LPS into the circulation. Apart from its role in modulating the composition of bacteria, it can also function to influence intracellular signaling.